(untitled) (Medical Forum Monthly, 2024)
Objectives: To determine maternal outcome in terms of morbidity and mortality in cases of placenta praevia to determine the fetal outcome regarding morbidity and mortality in placenta praevia. Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the Aziz Bhatti Shaheed Hospital NSMC, University of Gujrat, for a period of one year 2015 and 2016. Materials and Methods: Two types of patients were included in the study.The booked patients who were diagnosed by routine ultrasonography as cases of placenta praevia and the patients who presented with vaginal bleeding and were diagnosed by ultrasonography. The babies were followed up for seven days and maternal condition for six weeks after delivery. Results: Total no of the patients included in this study was 104 and was done for a period of one year 2015-16at Aziz Bhatti Hospital NSMC Gujrat. Majority of the patients who presented were multigravida and none of the primigravida had placenta previa. Mean gestational age was 33.4 weeks, 1.92% of the cases had previous c-section. The patients who required admission for more than once were 19.23%, 46.15% of the patients had previous episode of bleeding. The patients who required blood transfusion were 65.3%. Eighty four percent patient had c section and the patient with PPH were 7.69%, 1.92% had cesarean hysterectomy and one patient died because of hemorrhage. The incidence of premature deliveries was 55.76% , and the percentage of the neonates who died because of this were 11.53%. Conclusion: It is concluded, that in a country like ours, placenta praevia is still one of the important causes of fetal mortality and maternal morbidity. These cases should be screened and should be managed expectantly as suggested by Macaffe. These cases should by managed in centres where facilities for advanced sugery,specialized anesthesia, ICU, blood transfusion and blood products and neonatal intensive care units are there and system should be backed by a proper referral facility.